Investigation of ion transport and electrochemical performance of fluorinated and lithiated gel polymer electrolytes for lithium ion batteries - Shubha Nageswaran (2015)
One of the main challenges that restrict the large scale application of lithium ion batteries for high energy and high power density applications is the electrolyte. An electrolyte that has high ionic conductivity, high lithium ion transference number, and good mechanical and thermal stability is the need of the day. Polymer based electrolytes offer several advantages such as easy processibility, good mechanical properties and reasonable ionic conductivity. Amongst the polymer electrolytes, gel polymer electrolytes (GPEs) are most promising, because they offer comparable performance to the currently used commercial liquid electrolytes, while offering the added advantage of shape flexibility. However, there are still several issues that need to be tackled before the GPEs can be put to large scale commercial use. This thesis focusses on the study of GPEs for application in lithium based batteries. High ionic conductivity poly (vinylidene fluoride-co-hexafluoropropylene) (P(VdF-co-HFP)) based GPEs and high lithium transference number poly (4-lithium styrene sulfonic acid) (PSSLi) based gels were explored as alternate electrolytes. The main problem associated with P(VdF-co-HFP) based GPEs is the mutual exclusivity of ionic conductivity and mechanical properties. The main problem with the PSSLi based gels is lower ionic conductivity, due to the reduced number of mobile charge carriers. This thesis mainly focusses on addressing the two most common issues affecting gel polymer electrolytes-improving the electrochemical properties while maintaining the mechanical integrity and improving the lithium ion transference number without affecting the ionic conductivity. The effect of adding fillers and a second polymer to improve the ionic conductivity while maintaining the mechanical properties was explored. The ionic conductivity of gel polymer electrolytes is affected by several factors. The various factors which affect ionic conductivity were compared and the factors that have the most pronounced effect were identified. The effect of reduced ionic coupling, increased lithium ion dissociation and increased chain segmental motion on the ion transporting abilities of the P(VdF-co-HFP) GPE and PSSLi gel was systematically studied. It was seen that increased lithium dissociation was the best approach to obtain liquid like conductivity. The ionic conductivity at 30 °C of the P(VdF-co-HFP) GPEs increased from 2.9 mS/cm to 9.6 mS/cm, while for the PSSLi system the conductivity improved from 1.4 mS/cm to 2.5 mS/cm. The transference number of the P(VdF-co-HFP) GPEs improved from 0.42 to 0.68 leading to increased lithium transport. Based on the results, it was seen that the mechanism of ion transport in the two systems was very different. The P(VdF-co-HFP) GPEs resembled the commercially used liquid electrolytes. Ionic conductivity in these systems was mainly dependent on increasing the lithium ion concentration in the system. However, in the PSSLi gel, it was seen that beyond an optimum concentration of lithium, the ionic conductivity begins to drop. To account for this behaviour,fundamental studies on the ion transport mechanism of PSSLi based gels was undertaken using NMR and AC impedance. The mechanism by which the fillers and blends affect the ion transport in PSSLi gels was also elucidated. The effect of using high transference number PSSLi on the high rate performance of the lithium ion battery was also examined.